Seven Years Cognitive Functioning and Early Assessment in Extremely Low Birth Weight Children - Squarza, Chiara; Picciolini, Odoardo; Gardon, Laura; Ravasi, Maura; Giannì, Maria L.; Porro, Matteo; Bonzini, Matteo; Gangi, Silvana; Mosca, Fabio (Frontiers in Psychology, 2017)
Infants born preterm are at high risk for the onset of cognitive dysfunctions at school age. The aim of this study was to investigate the association between early neurodevelopmental assessment and the risk of adverse cognitive outcome in extremely low birth weight children. We enrolled all newborns (January 2002 – April 2007) consecutively admitted to our Institution, with a birthweight < 1000 g. Exclusion criteria were genetic abnormalities, severe neurofunctional impairment, and/or neurosensory disabilities. 99 children were assessed at 1 year of corrected age using the Griffiths Mental Development Scales Revised. The same children were re-assessed at school age through the Wechsler Intelligence Scale for Children. Children with impaired Griffiths General Quotient (i.e. < 1 Standard Deviation) at 1 year of corrected age showed a significantly lower Full Scale Intelligence Quotient at 7 years of chronological age when compared to children who scored in the normal range at 1 year (p < 0.01). Considering the Griffiths Sub-quotients separately, a poor score in the Performance or in the Personal-Social Sub-quotients at 1 year was associated with significantly worse cognitive outcomes both in the Verbal and in the Performance Intelligence Quotients at 7 years (p < 0.01 and p < 0.05 respectively). A score < 1 Standard Deviation in the Locomotor or in the Eye and Hand Coordination Sub-quotients were specifically associated with poorer Performance or Verbal Intelligence Quotients respectively (p < 0.05). Our findings suggest that a poor score on the Griffiths Scales at 1 year is associated with a higher risk of cognitive impairment at school age. Larger confirmation studies are needed.